What is the result of adding these two equations?
\begin{aligned} -5x-9y &= 3 \\\\ 5x-9y &= -2 \end{aligned}
−5x−9y
5x−9y


=3
=−2

Respuesta :

The result is the point:

[tex]\left(-\frac{1}{2},\frac{1}{18}\right)[/tex]

Explanation:

In this exercise we have two equations:

[tex]\left \{ {{-5x-9y=3 } \atop {5x-9y=-2}} \right.[/tex]

So when adding these two equations we have:

[tex]-5x-9y+(5x-9y)=3+(-2) \\ \\ \\ Combine \ like \ terms: \\ \\ (-5x+5x)+(-9y-9y)=3-2 \\ \\ -18y=1 \\ \\ y=-\frac{1}{18}[/tex]

Substituting y into equation 1:

[tex]-5x-9y=3 \\ \\ -5x-9(-\frac{1}{18})=3 \\ \\ Solving \ for \ x: \\ \\ 5x=\frac{9}{18}-3 \\ \\ 5x=-\frac{5}{2} \\ \\ x=-\frac{1}{2}[/tex]

So the solution of this system of equations is the point:

[tex]\left(-\frac{1}{2},\frac{1}{18}\right)[/tex]

Learn more:

System of equations: https://brainly.com/question/13799715

#LearnWithBrainly

Answer:

-18y=1

Step-by-step explanation:

Did it on Khan Academy

ACCESS MORE